Pembiasaan Kegiatan Muhadharah sebagai Upaya Meningkatkan Percaya Diri Siswa di MAN 2 Karawang - Cuncun Angga Resta; Tajuddin Nur; Yayat Herdiana (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
This research is motivated by the lack of students’ self-confidence to speak in front of the public in conveying something good. Such as: lectures or speeches or other useful perfomances. Espesially in this sophisticated era, students are more confident to post something that is less useful than to appear confident in public. This can be seen from the muhadharah activities carried out by MAN 2 Karawang there are still students who have stage fright shen given an assignment. This study has a purpose, namely to determine the implementation of habituation of muhadharah activities as an effort to increase student confidence in MAN 2 Karawang. Researxhers used qualitative methods. The informans of this study were supervicing teachers and students of the muhadharah activities. Data collection techniques used are observation, interviews and documentation. After the data is collected, it is analyzed using inductive methods including: data reduction, data presentation, and drawing conclusions. And the results of this study are that muhadharah activities are carried out once a week avery Friday at 13.00 until finished. by holding this activity, it can increase students'’self-confidence and train students’ courage or mentality. Not just speeches, students are given tasks ranging from MC, saritilawah, entertainment such as hadroh, sholawat or poetry and reading closing prayers. And after the end of the activity, the suoervising teacher always provides motivation or evalution regarding the course of muhadharah activities on the same day and for the future.